2012
DOI: 10.1371/journal.pone.0048543
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Chelation Reduces Hippocampal Neurogenesis after Pilocarpine-Induced Seizure

Abstract: Several studies have shown that epileptic seizures increase hippocampal neurogenesis in the adult. However, the mechanism underlying increased neurogenesis after seizures remains largely unknown. Neurogenesis occurs in the subgranular zone (SGZ) of the hippocampus in the adult brain, although an understanding of why it actively occurs in this region has remained elusive. A high level of vesicular zinc is localized in the presynaptic terminals of the SGZ. Previously, we demonstrated that a possible correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…Our in vitro assays demonstrated that clioquinol, phenanthroline, and TPEN were the most effective independently of fungal growth stage, and they were selected for use in vivo. They all produced complete inhibition of fungal growth at low concentrations and have been previously used in animal models (18,30,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our in vitro assays demonstrated that clioquinol, phenanthroline, and TPEN were the most effective independently of fungal growth stage, and they were selected for use in vivo. They all produced complete inhibition of fungal growth at low concentrations and have been previously used in animal models (18,30,33).…”
Section: Discussionmentioning
confidence: 99%
“…(i) Clioquinol (5-chloro-7-iodo-quinolin-8-ol) is a halogenated 8-hydroxyquinoline (14). It was selected because it has been extensively used as a zinc chelator both in vitro and in vivo (15)(16)(17)(18)(19). Clioquinol (Fluca, 33931-100MG-R) was diluted to a 0.05 M stock solution in 100% dimethyl sulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn 2+ release from the Schaffer collateral/ commissural pathway plays a key role for the increase in cytosolic Zn 2+ in the CA1. On the other hand, dentate granule cells are insensitive to neurodegeneration (Kim et al, 2012;Noh et al, 2005). The insensitivity might be due to the minimal innervation of zincergic neurons to dentate granule cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the present study, we did not use an unbiased stereological method to quantify DCX positive cells, that is a limitation of the approach. Most studies evaluate DCX expression after 3 to 4 weeks after seizures, since a marked increase on hippocampal proliferation after pharmacological induction of seizures in rodents is only detected after 7-9 days after the insult (Gu et al, 2010;Jessberger et al, 2005;Kim et al, 2012;Walter et al, 2007). Interestingly, PI3KÎł −/− animals exhibited a significant decrease in the number of hippocampal DCX + cells after pilocarpine.…”
Section: Discussionmentioning
confidence: 99%